Phenakite and bertrandite: products of post-magmatic alteration of beryl in granitic pegmatites (Tatric Superunit, Western Carpathians, Slovakia). (18th October 2022) - Uher, Pavel; Ozdín, Daniel; Bačík, Peter; Števko, Martin; Ondrejka, Martin; Rybnikova, Olena; Chládek, Štěpán; Fridrichová, Jana; Pršek, Jaroslav; Puškelová, Ľubica
Abstract: The beryllium silicate minerals phenakite and bertrandite have been identified in granitic pegmatite dykes of the beryl-columbite subtype of Variscan age ( 340−355 Ma), associated with S- to I-type granitic rocks of the Tatric Superunit, Western Carpathians (Slovakia). The two beryllium silicates and associated minerals were characterised by electron microprobe analysis, back-scattered electron petrography and cathodoluminescence imagery, X-ray diffraction and micro-Raman techniques. Phenakite and bertrandite form euhedral-to-anhedral crystals and aggregates in irregular domains and veinlets replacing primary magmatic beryl. A detailed textural study revealed a close genetic association of phenakite and bertrandite with secondary fine-grained quartz, K-feldspar and muscovite. Locally, clay phyllosilicate minerals, (with compositions similar to those of Fe-dominant hydrobiotite, beidellite, nontronite and saponite) occur as the youngest minerals. During the post-magmatic (hydrothermal) stage of the pegmatites, infiltration of aqueous K-bearing fluids at T ≈ 200–400°C resulted in the breakdown of magmatic beryl to secondary assemblages containing phenakite and bertrandite.